Technostress among Boomer Teachers in ICT Integration - Lozada, Iris; Almerez, Queenie Lyn; Trinidad, Amelie (Journal of Interdisciplinary Perspectives, 2025)
The rapid advancement of information and communication technology (ICT) has significantly transformed teaching and learning environments, often leading to technostress among educators. While existing studies explore ICT integration challenges, limited research focuses on boomer teachers' experiences in managing technostress. This study examines the experiences of boomer teachers in integrating ICT in the classroom, their coping mechanisms, and insights on mitigating technostress. Utilizing a qualitative phenomenological approach, the study involved eight boomer teachers from large public secondary schools in Davao del Sur. Participants were selected through purposive sampling based on specific criteria: (1) belonging to the boomer generation, (2) actively teaching in a public secondary school, (3) integrating ICT in classroom instruction, and (4) willingness to participate in semi-structured interviews. Thematic analysis of the data revealed that boomer teachers face challenges such as technological incompetency, adaptability issues, and unequal access to ICT resources, which hinder their effective use of technology in teaching. However, strategies including collaborative learning, ICT training, and resilience-building helped mitigate technostress. The study highlights the importance of continuous professional development, mentorship programs, and intergenerational collaboration to support boomer teachers in overcoming ICT-related challenges. Furthermore, promoting a culture of lifelong learning and providing institutional support can enhance ICT integration and overall teaching effectiveness. The study recommends further quantitative research and a broader participant base to validate and extend these findings. These insights contribute to developing targeted training programs and policies to reduce technostress and improve digital competence among older educators.